Assessment of postnatal depression and some associated risk factors among mothers attending the immunisation outpatient department in a tertiary health care centre: a cross sectional study - Gaikwad, Shruti; Mundada, Vinod; Dhande, Vishal; Doibale, Mohan (International Journal Of Community Medicine And Public Health, 2019)
Background: Postpartum depression is a signiﬁcant and common health problem that causes a considerable amount of impact to both the mother and baby and distress on the family and society. The objective of this study is to find out prevalence of postnatal depression among mothers attending immunization outpatient department (OPD) for immunization of their baby in a tertiary health care center and to study some risk factors responsible for it. Methods: This cross sectional study was conducted in a tertiary care teaching hospital of Maharashtra state during period September to February 2019. Total 188 mothers were screened for postpartum depression using local version of EPDS (Edinburgh Postnatal Depression Scale). Results: 24 (12.76%) mothers were found to have a score of 10–12 indicating moderate depressive symptoms, and 18 mothers had a score of 13 and above. (9.57%). Risk factors found to be significantly associated with postnatal depression rural residence of mother, lack of support during and after pregnancy, history of domestic abuse, and stressful life events in the past year. Conclusions: Since the prevalence of EPDS score >13 was found to be high in the current study, we recommend routine screening for PPD in our population.